Mechanical properties and failure deformation mechanisms of yak horn under quasi-static compression and dynamic impact. (July 2020) - Liu, Shengfu; Xu, Shucai; Song, Jiafeng; Zhou, Jianfei; Xu, Lihan; Li, Xiujuan; Zou, Meng
Abstract: In the natural environment, the horns of yak possess remarkable structural mechanical properties to protect the head from injury. In this paper, quasi-static compression and dynamic impact tests were conducted on yak horn in different regions under axial and lateral conditions to evaluate mechanical properties such as elastic modulus, ultimate strength and energy absorption. Meanwhile, the failure deformation mechanism under both low and high strain rates is explored. Moreover, experimental analysis of the correlation among mechanical properties, sampling position, strain rate and loading direction was conducted. Fracture surface of horn was observed with the scanning electron microscope (SEM). Research data demonstrate that specific energy absorption and mechanical properties are correlated with sampling position. Under quasi-static compression and dynamic impact, clear anisotropy behavior of horn was observed, which is evidently reflected in the load-displacement curve. Mechanical properties such as elastic modulus and ultimate strength are different under quasi-static compression and dynamic impact. The failure mode of lamellar buckling and delamination existed in the axial failure process. Brittle fracture and extrusion densification occurred more frequently in the process of lateral failure.